Pluralism Values in The History of Islamic Culture (Analysis Study on Teaching Material of Class XII Madrasah Aliyah) - Arfan Mu'amar (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
This study aims to find out how and whether or not there are pluralismvalues in the history of Islamic culture in the analysis of teaching materialsof Class XII madrasah aliyah/Senior High School, therefore this research usedqualitative or library research methods because this study examines the sourcesthat comprise the literatures related to the title. The type of research is library(library research), because this study examines the data sources that compriseliterature related to the title. This research used analytical, comparative andcritical descriptive approach to qualitative data. The results of the analysis ofpluralism values contained in teaching materials of Islamic Culture History inClass XII is there are some material that is in accordance with pluralism wherein the material is very tolerant to multiculturalism that is accompanied byreligious pluralism, so that it become the achievement of harmony and mutualrespect and those that do not describe the existence of religious pluralism,because the material is widely known to the parties who want to damage goodrelations between religions and also fight over power by using the name ofreligion, and it does not accompanied by tolerance so that enmity betweenreligions happened. This shows that there are pluralism values in the Historyof Islamic Culture of Class XII teaching materials, although on the other handthere are those that do not show Pluralism values.